FORMATION OF THE CONCEPT OF HEDONISM AND ITS REPRESENTATION (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
This article thesis describes the history of the emergence of the philosophical term hedonism, which expresses the feeling that a happy life, which a person strives for throughout his life, is formed from the well-being of life. It also describes its historical development and forms of manifestation.